Serbia 1914, Poland 1939. A comparison - Ščepanjski, Vojćeh S. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The circumstances of implicating Serbia (in 1914) and Poland (in 1939) into world wars by the forces provoking these conflicts, as well as the history of the heroic resistance of both mentioned organisms against the aggressors having numerous advantages, deserve to be constantly reminded as great lessons for the next generations of Europeans. The anniversaries of the break out of both world wars constitute a great opportunity for this type of reminder. In the presented text, compiling the Serbian experiences of the war started in 1914 with the Polish experience of the war which broke out a quarter of century later, the author stresses the following issues: - the reaction of Serbia/Poland on declaring the wars 1914/1939 (in detail), and also (in general): - the situation of war seclusion of Serbia/Poland in 1914/1939 experienced despite having the allies, - huge discrepancies of the aggressors’ and the defenders’ forces, as well as the resistance, exceeding the estimated opportunities, of the attacked countries towards the enemies, - the scale of the Serbian martyrdom in the 1st and Polish in the 2nd world wars, - the appearance of the war success, redeemed with extremely great sacrifice, and the presence of the threat for the Serbian/Polish nation in the order shaped as a result 1st/2nd world war. The fragments of sources quoted in the article as well as the authors’ considerations, are exhibited as key terms and simultaneously as the common features of the Serbs and the Poles, enhanced at the moments of threat for both the nations and their countries: faith (in victory, in the help of Providence), honour, the spirit of fight and being ready for uncompromising resistance to aggressors. These values constitute an essential element of comparison in the search of understanding the Serbian and Polish history and attitudes as well as the choices made by the Serbs and the Poles.
Keywords: war martyrdom; resistance; Germany; Austro-Hungarian Monarchy; Poland; Serbia; Polish war in 1939; Austro-Hungary and Serbia conflict in 1914; Second World War; First World War